Demonstration Method as An Effort to Improve Understanding of Financial Report Analysis Cooperative of Boarding School at Darul Ittihad Boarding School Bangkalan - Ghofirin, S.Pd., M.Pd, Mohammad; Dina Anggraeni Susesti (Universitas Nahdlatul Ulama Surabaya, 2025)
The rapid development cottage Islamic boarding schools in Indonesia are reflected from growth amount Islamic boarding schools are increasingly many, spread across various regions, both urban and rural isolated. For ensure the learning process at the boarding school Islamic boarding school walk effective, important for cottage Islamic boarding school for own adequate facilities​ for the students besides as place stay they. Very good facilities required like room study and dormitory for student own importance alone. Not only that, cottage Islamic boarding schools must also equipped with facility economy like cooperative For fulfil need daily santri . As entity economy in​ cottage Islamic boarding school, report finance cooperative become attention main Because related close with health finance cooperative . Method in study This use method demonstration with four stages , (1) Needs analysis ; (2) Planning Training ; (3) Implementation Training ; (4) Assessment Plate i han. The result of study This is increasing understanding manager cooperative cottage Islamic boarding school Darul Ittihad in serve report finance with pattern sharia . Improvement knowledge that has been owned by participants from manager cooperative cottage Islamic boarding school Darul Ittihad Bangkalan potential can used For face challenges and problems that have been This often experienced by cooperatives cottage Islamic boarding school with pattern sharia in Indonesia.